Learning‐driven cerebellar intrinsic functional connectivity changes in men. Issue 4 (24th November 2019) - Edde, Manon; Di Scala, Georges; Dupuy, Maud; Dilharreguy, Bixente; Catheline, Gwenaëlle; Chanraud, Sandra
Abstract: Learning involves distributed but coordinated activity among the widespread connected brain areas. Increase in areas connections' strength may be established offline, that is, aside from the task itself, in a resting‐state. The resulting functional connectivity may hence constitute a neural trace of the learning episode. The present study examined whether a conditional visuomotor learning task previously shown to activate the cerebellum would modify cerebellar intrinsic connectivity in groups of young and older male subjects. In the group of young subjects, resting‐state connectivity within several cerebellar networks (fronto‐cerebellar, temporo‐cerebellar, cerebello‐cerebellar) was modified following the task. In most cases, modulation resulted in increased anticorrelations between cerebellar and cortical areas and the amplitude of changes was correlated with learning efficacy. The group of older subjects drastically differed, with sparser modifications of resting‐state functional connectivity and no cerebellar networks involved. The findings of this exploratory study indicate that associative learning modifies the strength of intrinsic connectivity in young subjects but to a lesser degree in older subjects. They further suggest that functional connectivity within cerebellar networks may play an operative role in this kind of learning. Abstract : The figure illustrates the Resting State Connectivity changes in young male subjects. Following a conditional visuo‐motor learning task, increased anticorrelations between cerebellar and cortical areas were found. All together, our results suggest that the connectivity changes play an operative role in learning.